2007
DOI: 10.2353/ajpath.2007.070345
|View full text |Cite
|
Sign up to set email alerts
|

Early Axonopathy Preceding Neurofibrillary Tangles in Mutant Tau Transgenic Mice

Abstract: Neurodegenerative diseases characterized by brain and spinal cord involvement often show widespread accumulations of tau aggregates. We have generated a transgenic mouse line (Tg30tau) expressing in the forebrain and the spinal cord a human tau protein bearing two pathogenic mutations (P301S and G272V). These mice developed age-dependent brain and hippocampal atrophy, central and peripheral axonopathy, progressive motor impairment with neurogenic muscle atrophy, and neurofibrillary tangles and had decreased su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
106
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 74 publications
17
106
0
Order By: Relevance
“…The K3 mice present with earlyonset memory impairment at an age of 4 months, before Bielschowsky-positive tau deposits are detectable. This is in line with the observation that memory deficits precede histopathological changes in other tau-expressing strains (21,42). Pathological tau thus interferes with distinct cellular mechanisms causing neuronal dysfunction before tau is sequestered into deposits.…”
Section: Discussionsupporting
confidence: 88%
“…The K3 mice present with earlyonset memory impairment at an age of 4 months, before Bielschowsky-positive tau deposits are detectable. This is in line with the observation that memory deficits precede histopathological changes in other tau-expressing strains (21,42). Pathological tau thus interferes with distinct cellular mechanisms causing neuronal dysfunction before tau is sequestered into deposits.…”
Section: Discussionsupporting
confidence: 88%
“…In line with this view, in mice over-expressing mutated human tau, NFT formation is preceded by axonopathy in the absence of amyloid plaque formation. 138 Moreover, genetic ablation of kinesin light chain 1, which induces an age-dependent axonopathy, is accompanied by tau hyperphosphorylation, as evaluated using several AD-specific tau antibodies. 138 …”
Section: Formation Of Neurofibrillary Tanglesmentioning
confidence: 99%
“…138 Moreover, genetic ablation of kinesin light chain 1, which induces an age-dependent axonopathy, is accompanied by tau hyperphosphorylation, as evaluated using several AD-specific tau antibodies. 138 …”
Section: Formation Of Neurofibrillary Tanglesmentioning
confidence: 99%
“…inhibited fast axonal transport in isolated axoplasm [41]. Transgenic mice overexpressing human wild-type tau [45] or mutant tau [27] also developed axonal swellings suggestive of defects in axonal transport. In vitro motility assays suggested that tau influences the rate of attachment and detachment of motor proteins along microtubules [15,47].…”
Section: Introductionmentioning
confidence: 99%